Production and physicochemical evaluation of a pure malt craft beer with the addition of Extracts of Syzygium aromaticum and Cinnamomum zeylanicum (Research, Society and Development, 2020)
This work produced a pure malt craft beer following the characteristics of the German Pilsen style with the addition of the extracts of Syzygium aromaticum (clove) and Cinnamomum zeylanicum (cinnamon) the formulation of the produced beverage. For the production of the beverage, the processes of malt grinding, showing, clarification, boiling, cooling, fermentation, maturation, carbonation and fill were used. According to the results, the beer was classified according to the legislation according to the characteristics of the fermentation and the finished product and, when evaluating the parameters primitive extract, it was observed that the result of 12.21 can be classified as extra beer (EP ≥ 12% and ≤ 14%); alcohol in volume (%v/v), which obtained a result of 5.2, was classified as beer of high alcohol content, and that falls within the limit of the German Pilsen style, 4.4 to 5.2%. Regarding bitterness, the value of 17.82 is below the limit range specified by the Beer Judge Certification Program – BJCP, but within the range of a Belgian Blonde Ale (IBU between 15 and 30). The preparation of beer using differentiated ingredients added characteristic attributes to the product. With this, the development of these products with varied flavors and aromas meets the current needs of the consumer.